2014
DOI: 10.1386/jgvw.6.2.143_1
|View full text |Cite
|
Sign up to set email alerts
|

Gamification as twenty-first-century ideology

Abstract: Gamification as the process of turning extra-ludic activities into play can be seen in two different ways: following Bataille, we would hope that play could be a flight line from the servitude of the capital-labour relationship. Following Adorno and Benjamin, however, we might discover that the escape from the drudgery of the worker leads to an equally alienating drudgery of the player. I argue that gamification might be seen as a form of ideology and therefore a mechanism of the dominant class to set agenda a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Emil refers to indie games as “an art form,” which is contrasted to the “old industry.” Such narratives underscore that indie labor is “different” and indeed “not quite work.” As Mathias Fuchs (2014, 153) asserts in the context of gamification, “the attempt to harmonize play and labour, however, is ideology.” My participants’ belief that they are less able to address racism than their indie counterparts rests on a perception of indie game development as more play than work, and in turn allows AAA developers to believe they lack power to change representational patterns in the game industry.…”
Section: Creative Destruction: Precarious (Indie) Labormentioning
confidence: 99%
“…Emil refers to indie games as “an art form,” which is contrasted to the “old industry.” Such narratives underscore that indie labor is “different” and indeed “not quite work.” As Mathias Fuchs (2014, 153) asserts in the context of gamification, “the attempt to harmonize play and labour, however, is ideology.” My participants’ belief that they are less able to address racism than their indie counterparts rests on a perception of indie game development as more play than work, and in turn allows AAA developers to believe they lack power to change representational patterns in the game industry.…”
Section: Creative Destruction: Precarious (Indie) Labormentioning
confidence: 99%
“…Less players, or even workers, and more like the mindless gamblers ‘who live their lives as automatons … who have completely liquidated their memories’ (Benjamin, 2003: 330–331), play can be transformed into labour as we tap, swipe, move and stroke. Benjamin and Adorno both talk of the labour of play (Fuchs, 2014), except that here, between the watch and the user, labour and the machine are not just producing but also liquidating recollections that do not belong to the canon of digital memory (Frith and Kalin, 2015), embodied actions that leave no after image (Jameson, 1992: 76) – just the emptiness of repetitive labour.…”
Section: Where Is My Watch Where Is My Attention? From Play To Labourmentioning
confidence: 99%
“…This issue is actually Toplum ve Sosyal Hizmet Cilt 32, Sayı 2, Nisan 2021; s. 589-606 596 related to macro social work, which is practiced in the society or communities. Therefore, although this is a new issue, there are studies showing that gamification can be used for different purposes such as transforming the society, conforming and shaping the social structure or adopting ideologies (Fuchs, 2014;Schrape, 2014;AlBalawi, AlSaawi, AlTassan and Fakeerah, 2015;Devisch, Poplin and Sofronie, 2016). In this part of the study, other than these studies, predictions about the future of macro social work will be revealed through a gamification project implemented in China.…”
Section: Gamification Of Human Lifementioning
confidence: 99%